Faktor–Faktor yang Mempengaruhi Abnormal Return Saham pada Kinerja Jangka Panjang Penawaran Umum Perdana - Dion Antonio; Nelson Hamonangan; Siti Ruhana Dara (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2023)
This study means to decide the impact of Magnitude of undervaluing, Benhmark, Money raised, Market esteem, firm size, firm age on unusual stock profits from the drawn out exhibition of the first sale of stock. The fact that match the measures makes the model utilized by the specialist is a purposive testing technique, so through 157 recorded organizations directing starting public contributions in the 2010 2019 period, 121 organizations chosen. SPSS 24 programming is utilized by analysts to dissect information utilizing various straight relapse. The aftereffects of the review make sense of that the greatness of undervaluing, cash raised, market esteem affects strange returns. Benhmarks, firm size, firm age meaningfully affect unusual returns.